Orai3 channel is the 2-APB-induced endoplasmic reticulum calcium leak. (July 2017) - Leon-Aparicio, Daniel; Pacheco, Jonathan; Chavez-Reyes, Jesus; Galindo, Jose M.; Valdes, Jesus; Vaca, Luis; Guerrero-Hernandez, Agustin
Graphical abstract: Highlights: Orai3 channels colocalize with IP3 Rs in the endoplasmic reticulum. 2-APB activates Orai3 channels in the endoplasmic reticulum. Orai3 channels do not participate in the ER Ca 2+ leak revealed by thapsigargin.. Orai3 channels might have a role in limiting Ca 2+ overload of the ER store. Abstract: We have studied in HeLa cells the molecular nature of the 2-APB induced ER Ca 2+ leak using synthetic Ca 2+ indicators that report changes in both the cytoplasmic ([Ca 2+ ]i ) and the luminal ER ([Ca 2+ ]ER ) Ca 2+ concentrations. We have tested the hypothesis that Orai channels participate in the 2-APB-induced ER Ca 2+ leak that was characterized in the companion paper. The expression of the dominant negative Orai1 E106A mutant, which has been reported to block the activity of all three types of Orai channels, inhibited the effect of 2-APB on the [Ca 2+ ]ER but did not decrease the ER Ca 2+ leak after thapsigargin (TG). Orai3 channel, but neither Orai1 nor Orai2, colocalizes with expressed IP3 R and only Orai3 channel supported the 2-APB-induced ER Ca 2+ leak, while Orai1 and Orai2 inhibited this type of ER Ca 2+ leak. Decreasing the expression of Orai3 inhibited the 2-APB-induced ER Ca 2+ leak but did not modify the ER Ca 2+ leak revealed by inhibition of SERCA pumps with TG. However, reducing the expression of Orai3 channel resulted in larger [Ca 2+ ]i response after TG but only when the ER store had been overloaded with Ca 2+ by eliminating the acidic internal Ca 2+ store with bafilomycin. These data suggest that Orai3 channel does not participate in the TG-revealed ER Ca 2+ leak but forms an ER Ca 2+ leak channel that is limiting the overloading with Ca 2+ of the ER store.